Regional Bank Intermediation Function Through Deposit and Credit Products - Ambarwati Akib (Phinisi Applied Accounting Journal, 2026)
Purpose: This study aims to analyze the intermediation function of a regional bank through deposit and credit products. Method: The study uses a descriptive qualitative approach with a case study design at one regional bank branch office in South Sulawesi. Data were collected through interviews, documentation, and literature review, and were analyzed thematically by classifying the findings into fund mobilization, credit distribution, digital services, and prudential banking practices. Findings: The findings indicate that the regional bank performs its intermediation function through current accounts, savings, time deposits, and deposits from other banks as funding instruments, while credit is distributed to civil servants, government contract employees, regional legislative members, retirees, regional-owned enterprise employees, and micro, small, and medium enterprises. The findings also show that intermediation is not merely a transfer of funds from depositors to borrowers. It is shaped by compliance, risk control, digital banking services, and credit feasibility assessment. The implementation of Know Your Customer, Anti-Money Laundering, Financial Information Service System checks, and the 5C principles reflects the bank's attempt to balance service expansion, operational security, and support for local economic activities. The study contributes to understanding regional bank intermediation as a practice that integrates funding, lending, governance, and public trust at the local level.